Is there Still Optimism for Law Enforcement in Indonesia? Critical Notes on the Book ‘Noda Hitam Hukum Indonesia' (Yogyakarta: Navila Idea, 2010) - Afruloh, Arif (Universitas Negeri Semarang, 2019)
This book written by Muhammad Awan explores the covert tactics of circumventing the law which were carried out systematically and procedurally during the reigns of President Susilo Bambang Yudhoyono and Jusuf Kalla. So that the law cannot do much against the actions that the author examines in this book. This book explains how the Bakrie Group was able to escape responsibility for the Lapindo Mudflow tragedy. We can also see a series of frauds in the 2009 election. It can be seen that there were attempts to undermine Bawaslu and Panwaslu, inflate the Permanent Voter List (DPT), or make Bank Century a place to keep illegal funds. Furthermore, when reading this book, we will understand that the principle of